Long-term effects of natalizumab on MRI activity and clinical outcomes in Japanese patients with relapsing-remitting multiple sclerosis - Takahiko Saida; Qi Hao; Michihiro Kanda; Yumiko Tani (BMC Neurology, 2023)
Abstract Background Relapsing-remitting multiple sclerosis (RRMS) is the most common phenotype of multiple sclerosis (MS), and its active stage is characterized by active T2 lesions with or without gadolinium (Gd) enhancement on magnetic resonance imaging (MRI). Natalizumab is indicated as monotherapy in adults with active RRMS in Japan. The main objective of this study was to investigate the long-term effect of natalizumab on disease progression in Japanese patients with RRMS using MRI data. Methods This retrospective, chart review study was conducted at a single center in Japan. The main study outcome was the yearly proportion of patients with active T2-weighted image lesions detected with or without Gd enhancement on brain MRI (incidence rate) after treatment initiation for up to 5 years. Additional endpoints included annual relapse rate (ARR) and expanded disability status scale (EDSS) score. Results This study included data from 85 patients with RRMS who had received natalizumab for ≥ 1 year; of these, 65 (76.5%) were female and the mean ± standard deviation (SD) age at baseline was 37.5 ± 10.0 years. The incidence rate of active T2 lesions was 52.9% (45/85) in the year prior to natalizumab treatment (Year − 1), which decreased to 2.4% and 1.6% in Year 0.5–1.5 and Year 1.5–2.5, respectively. No active T2 lesions were detected in Year 2.5–5.5 in patients who continued natalizumab treatment. EDSS score was stable, improved, and worsened in 61.8%, 26.3%, and 11.8% of patients, respectively. The median (range) EDSS score was 2.0 (0.0–7.0) at baseline (n = 85) and remained within a similar range (median score between 1.0 and 2.25 during Years 1–5). ARR decreased from 1.12 relapses per year at baseline to 0.12 relapses per year during Year 1 and remained below 0.15 relapses per year up to Year 5. Conclusion The results of this first long-term study evaluating the effect of natalizumab on MRI activity and clinical outcomes in Japanese patients with RRMS suggest that natalizumab markedly reduced disease activity and maintained effectiveness over several years.